From bench to bedside: The long journey of long non-coding RNAs. Issue 3 (June 2017) - Bonetti, Alessandro; Carninci, Piero
Abstract: Long non-coding RNAs constitute the major transcriptional output of human genome. They are conveniently defined as RNA molecules longer than 200 nucleotides and not encoding proteins. Recent studies have highlighted the central role played by these transcripts in several physiological and pathological processes. Here we highlight how long non-coding RNAs have been used for diagnostic and therapeutic approaches and discuss how in the near future we can envision their application as pharmacological agents. Highlights: Alterations of lncRNAs expression can lead to a wide variety of diseases. LncRNAs specificity can be exploited for the development of novel biomarkers. ASOs targeting lncRNAs can ameliorate disorders phenotypes in animal models. LncRNAs can modulate cell transcriptome and translatome.